Factors which influence performance of biology students in Gweru district secondary schools. - Shalongo, Otilie Oshoveli (Midlands State University, 2018)
The purpose of this study was to investigate the factors which influence performance of Biology students in Gweru District Secondary Schools. The study also aimed at finding out strategies which can be used to improve performance of students in Biology. Data was collected from three schools through questionnaires and interviews. A descriptive survey design was used during the study. This study comprised a sample of 15 participants and a total of 3 secondary schools in Gweru Urban District. The study targeted biology teachers and Head of Departments (science). Stratified random sampling was used to select schools; head of sciences department for Biology were purposively sampled. Datas were collected from 11 Biology teachers and 4 heads of department from different schools. Data collected were presented using tables and verbatim. The data was presented and analysed both quantitatively and qualitatively. The findings revealed that 100% of teacher respondents indicated that there are factors which influence the performance of students in Biology. The findings revealed that parents, learner’s profiles, physical resources, financial resources, home environment, language as medium of instruction, the lengthily syllabus and use of textbooks, educational resources at home, attitude, lack of datas, transformation process were the major factors that influence student’s performance in Biology in Gweru District Secondary Schools. The study further revealed that field work, team work, inquiry approaches, teacher competencies, resources centers and positive attitudes are some of the strategies that can be used to improve performance of students in Biology. The study recommends a special levy for Science should be introduced in schools to raise funds that can be used to purchase laboratory apparatus and ICT equipment necessary for teaching and learning sciences, The Provincial and District Offices should carry out constant and frequent supervision in schools to ensure that teachers implement policies that are in line with the teaching and learning of Biology at all levels especially on the provision of practical work. The Ministry of Primary and Secondary Education should organize seminars and workshops for Biology teachers.